Analytical validation using a gas mixing system for the determination of gaseous formaldehyde. Issue 43 (23rd October 2020) - Souza, Murilo de O.; Sánchez, Benigno; Fuentes, Marta; Gilaranz, Juan; Canela, Maria C.
Abstract : Formaldehyde levels in the atmosphere are a concern in the indoor and outdoor air and the DNPH-tubes are enable to analyse it with confiability. Abstract : Formaldehyde levels in the atmosphere are a concern in the indoor and outdoor air and many methods for determining this compound have been developed. The use of 2, 4-dinitrophenylhydrazine (DNPH) for reaction with formaldehyde, catalyzed by acid, forming a hydrazone derivative in cartridges is considered the standard method for analyzing formaldehyde compounds in the air. However, formaldehyde is quantified using an analytical curve, created by diluting liquid standards of the formaldehyde-DNPH product. The analysis aims to quantify the gas phase formaldehyde, and it may be subject to experimental biases from the differences in the matrix of the sample (gas) and calibration standard (liquid). The objective of this work was to build an analytical curve in the gaseous phase using a synthetic air/formaldehyde mixing system (SFMS) and sampling with SPE-DNPH-tubes, comparing with the analytical curve in the liquid phase adopted by the Environmental Protection Agency (EPA). Parameters of linearity, sensitivity, limit of detection (LOD), limit of quantification (LOQ), precision and accuracy (recovery) were determined from the analytical curve in the gaseous phase. The best recovery in DNPH-tubes was obtained using the range of 400–1600 mL min −1 of flow rates in the gaseous phase. The sampling and reaction/elution of formaldehyde using DNPH-tubes presented adequate linearity and a similar sensitivity in the liquid analytical curve. Considering the LOD and LOQ in the gaseous phase, the values in nanograms are higher than those in the liquid phase. This study suggests that the quantification of formaldehyde in ambient air may be subject to bias due to differences in derivatization reaction efficiency. However, the results prove the efficiency of formaldehyde recovery from the atmosphere and the validity of the use of this DNPH-tube method.